Main theoretical approaches on the issue of threat to democracy - Dziubenko, Yuliia; Дзюбенко, Ю. (Одеса : Фенікс, 2015)
The article analyzes main theoretical approaches of foreign and domestic scholars on the issue of threat to democracy («distortion of democracy», «non fulfillment of promises of democracy», «threats to democracy», «fragility of modern democratic regimes»). The author defines contemporary threats to democracy and the main threats to democracy in Ukraine which are: incomplete administrative reform; absence of a functioning system of distribution of power for three branches; collisions in legislation; low social mobility; low level of economic development; inability to influence the government; low effectiveness of democratic mechanisms to select elites and elected government institutions; social apathy, «syndrome of uncertainty».
Dziubenko Y. Main theoretical approaches on the issue of threat to democracy / Y. Dziubenko // Актуальні проблеми політики зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2015. – Вип. 56. – С. 92-98.
Keywords: загроза демократії; незавершеність адміністративної реформи; відсутність дієздатної системи розподілу трьох гілок влади; колізії у законодавстві; низька соціальна мобільність; низький рівень розвитку економіки; неспроможність впливати на владу; низька ефективність демократичних механізмів відбору еліт та виборних інститутів влади; соціальна апатія; «синдром невизначеності»; угроза демократии; незавершенность административной реформы; коллизии в законодательстве; низкая социальная мобильность; низкий уровень развития экономики; неспособность влиять на власть; низкая эффективность демократических механизмов отбора институтов власти; социальная апатия; «синдром неопределенности»; threat to democracy; incomplete administrative reform; absence of a functioning system of distribution of power for three branches; collisions in legislation; low social mobility; low level of economic development; inability to influence the government; low effectiveness of democratic mechanisms to select elites and elected government institutions; social apathy; «syndrome of uncertainty»